Application of choosing by advantages to determine the optimal site for solar power plants - Hui, Hwang Goh; Li, Chunyu; Zhang, Dongdong; Dai, Wei; Chee, Shen Lim; Kurniawan, Tonni Agustiono; Kai, Chen Goh (Nature Publishing Group, 2022)
Solar energy is a critical component of the energy development strategy. The site selection for solar power plants has a signifcant impact on the cost of energy production. A favorable situation would result in signifcant cost savings and increased electricity generation efciency. California is located in the southwest region of the United States of America and is blessed with an abundance of sunlight. In recent years, the state’s economy and population have expanded quickly, resulting in an increased need for power. This study examines the south of California as a possibly well-suited site for the constructing large solar power plants to meet the local electricity needs. To begin, this article imposed some limits on the selection of three potential sites for constructing solar power plants (S1, S2, and S3). Then, a systematic approach for solar power plant site selection was presented, focusing on fve major factors (economic, technological, social, geographical, and environmental). This is the frst time that the choosing by advantages (CBA) method has been used to determine the optimal sites for solar power plant construction, with the possible sites ranked as S2>S1 >S3. The results were then compared with traditional methods such as the multi-criteria decision-making method. The fndings of this study suggest that the CBA method not only streamlines the solar power plant site selection process but also closely aligns with the objectives and desires of the investors.